Assessing the hierarchy of personal values among adolescents: A comparison of rating scale and paired comparison methods. (13th February 2020) - Iijima, Yudai; Okumura, Yasuyuki; Yamasaki, Syudo; Ando, Shuntaro; Okada, Kensuke; Koike, Shinsuke; Endo, Kaori; Morimoto, Yuko; Williams, Aya; Murai, Toshiya; Tanaka, Saori C.; Hiraiwa‐Hasegawa, Mariko; et al.
ABSTRACT: Introduction: For assessing personal values, the rating scale method may not adequately reflect the hierarchical structure of personal values and tends to be influenced by response style bias. The paired comparison method is considered a promising alternative approach, because it engages comparative judgment and may reduce response style biases. The present study aimed to compare these two methods for assessing the hierarchy of personal values among adolescents. Methods: A total of 191 community‐dwelling adolescents aged 12–15 years old completed the rating scale and paired comparison version of the Brief Personalized Value Inventory. Descriptive statistics and latent class analyses were used to assess the difference between the rating scale and paired comparison methods. Results: The two methods yielded similar rankings and means for personal values. The number of subgroups identified by latent class analysis was higher in the paired comparison method than in the rating scale method (10‐class vs. 5‐class). In the results using the rating scale method, there was a subgroup with high scores on all personal values items. Conclusions: The paired comparison method captured substantially more heterogeneity in the hierarchy of personal values among adolescents compared to the rating scale, which may be influenced by response style bias.